Correlation between the biomechanical characteristics and stability of the 143D movement during the balance phase in competitive Tai Chi - Huang, Ruifeng; Ma, Yong; Lin, Shijie; Zheng, Weitao; Liu, Lin; Jia, Mengyao (Frontiers in Bioengineering and Biotechnology, 2024)
Objective To explore the biomechanical factors that affect the stability of athletes in the 143D balance phase of competitive Tai Chi. Method Vicon motion capture system, Kistler force platform, and Noraxon sEMG system were used. The stability index should be calculated. Pearson or Spearman Correlation tests were used to analyse associations between biomechanical factors and the stability index. Results (1) Medial lateral stability index(MLSI): A significant negative correlation is found between the ankle inversion angle of the supporting leg (SL) and MLSI (p < 0.05). (2) Anterior posterior stability index(APSI): Significant negative correlations are observed between the ankle intorsion angle, iEMG of the Gastrocnemius, and the muscle contribution rates of the Tibialis Anterior, External Oblique, and Gastrocnemius of the non-supporting leg (NL) with APSI (p < 0.05). The ankle dorsiflexion moment, iEMG of the Rectus Femoris and Tibialis Anterior, the muscle contribution rate of the Biceps Femoris, and RMS of the Gluteus Maximus of the SL also showed significant negative correlations with APSI (p < 0.05). Strong, significant negative correlations are identified between the hip intorsion angle, iEMG of the Tibialis Anterior, and RMS of the Rectus Femoris of the NL with APSI (p < 0.01). A strong significant negative correlation is also found between the RMS of the Biceps Femoris of the SL and APSI (p < 0.01). The knee extorsion angle of the NL is positively correlated with APSI(p<0.05). (3) Dynamic Postural Stability Index(DPSI): The knee adduction angle, iEMG of the Tibialis Anterior, and RMS of the Erector Spinae of the NL are significantly positively correlated with DPSI(p<0.05). The knee abduction and hip extension moments of the SL are significantly positively correlated with DPSI(p<0.05). Conclusions The ankle inversion angle of SL impacts left-right stability, while the NL’s hip and ankle intorsion angle, knee extorsion angle, exertion on core muscle and SL’s main muscles, and exertion of specific muscles of the NL affect anterior-posterior stability.The hip extension moment and knee abduction moment of SL; the knee adduction angle, the exertion on Tibialis Anterior and the activation of the Erector Spinae of NL, significantly affect the overall stability of athletes.